Pharmacognostic and pharmacological studies of Bombax ceiba thorn extract - Manish A. Kamble; Debarshi Kar Mahapatra; Disha M. Dhabarde; Ashwini R. Ingole (GarVal Editorial Ltda., 2017)
Context: Bombax ceiba is a large deciduous tree found in tropical and sub-tropical regions of Asia, Africa, and Australia. Traditional systems of medicine such as Ayurveda, Siddha and Unani have been highlighted the use of B. ceiba parts (bark, leaves, and flower) for the treatment of numerous ailments like algesia, hepatotoxicity, hypertension, HIV infections, fever, dysentery, inflammation, catarrhal affection, ulcer, acne, gynecological disorders, piles and urinary infections. However, no scientific pharmacognostic, phytochemical and pharmacological study has been reported for B. ceiba thorn. Aims: To study the pharmacognostic and pharmacological potentials of B. ceiba thorn extract. Methods: The physicochemical properties were determined using pharmacopoeial tests. The phytochemical screening was carried out using standard protocols. The in vitro anti-inflammatory activity was performed by human red blood cells stabilization method, in vitro anthelmintic activity by Pheretima posthuma method, in vitro antioxidant activity by DPPH scavenging method, and anti-microbial studies by agar streak dilution method against bacteria E. coli, B. subtilis, K. pneumonia, and fungi C. albicans and A. niger. Results: The hydroalcoholic thorn extract of Bombax ceiba (TEBC) showed significant anti-inflammatory (46.9% stabilization), anthelmintic (death at 59.22 min), in vitro anti-oxidant (41.62% inhibition), and anti-microbial activities (B. subtilis > E. coli > K. pneumonia; A. niger > C. albicans). Conclusions: The study revealed the physicochemical, photochemical and pharmacognostic features of thorn of the B. ceiba. The study also revealed the possession of different pharmacological potentials of extract.